2013
DOI: 10.1111/jre.12050
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interleukin‐17‐stimulated interleukin‐6 and ‐8 production by cranberry components in human gingival fibroblasts and epithelial cells

Abstract: Cranberry NDM inhibition of constitutive and IL-17-stimulated IL-6 and IL-8 production by gingival fibroblasts and epithelial cells suggests that cranberry components could be useful as a host modulatory therapeutic agent to prevent or treat periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 73 publications
6
20
1
Order By: Relevance
“…Short‐term exposure to G‐HSA or HSA caused no significant cytotoxic membrane damage resulting in LDH release (data not shown). In addition, our previous studies showed that NDM (≤ 500 μg/mL) and LPS (1 μg/mL), to which the cells were also exposed, caused no significant membrane damage to gingival fibroblasts . While neither G‐HSA nor HSA decreased cell viability, after 3 d exposure all G‐HSA concentrations increased MTT assay values by ~20–30% compared to control, but these values had returned to control level by day 6 (data not shown).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Short‐term exposure to G‐HSA or HSA caused no significant cytotoxic membrane damage resulting in LDH release (data not shown). In addition, our previous studies showed that NDM (≤ 500 μg/mL) and LPS (1 μg/mL), to which the cells were also exposed, caused no significant membrane damage to gingival fibroblasts . While neither G‐HSA nor HSA decreased cell viability, after 3 d exposure all G‐HSA concentrations increased MTT assay values by ~20–30% compared to control, but these values had returned to control level by day 6 (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…While neither G‐HSA nor HSA decreased cell viability, after 3 d exposure all G‐HSA concentrations increased MTT assay values by ~20–30% compared to control, but these values had returned to control level by day 6 (data not shown). Furthermore, exposure of the fibroblasts to NDM concentrations ≤ 100 μg/mL for as long as 6 d had no significant effect on cell viability, but after 6 d exposure 250 μg/mL significantly decreased viability by ~40%, and 500 μg/mL caused ~80% decrease (IC50 ≅275 μg/mL at 144 h) . P.g .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Expression of IL-17 receptors A and C (IL-17RA and IL-17RC) has been shown on gingival epithelium cells, gingival fibroblasts and PDL fibroblasts (Hosokawa et al 2009b, Takahashi et al 2011, Zhu et al 2011. The receptor expression is functional as IL-17 stimulation induced production of IL-6, IL-8/ CXCL8, CCL20, pro-MMP1 and MMP3 by human gingival fibroblasts (Takahashi et al 2005, Beklen et al 2007, Hosokawa et al 2009b, Konermann et al 2011, Tipton et al 2013; and IL-1b, IL-6 and IL-8/CXCL8 production by gingival epithelial cells (Takahashi et al 2011, Tipton et al 2013. Stimulation with IL-17 in combination with other cytokines, such as IFN-c, TNF-a or IL-22 enhanced the pro-inflammatory cytokine production by these stromal cells (Beklen et al 2007, Mahanonda et al 2008, Hosokawa et al 2009a).…”
Section: Potential Drivers Of Th17 Cells/il-17 Responses In Gingival mentioning
confidence: 98%